2014
DOI: 10.1177/1077546314533579
|View full text |Cite
|
Sign up to set email alerts
|

Accurate method for harmonic responses of non-classically damped systems in the middle frequency range

Abstract: This paper is aimed at eliminating the influence of the problem of the harmonic response analysis of non-classically damped systems with lower-higher-modal truncation. Based on the Neumann expansion theorem and the frequency shifting technique, the relationships satisfied by eigensolutions and system matrices are established and an explicit expression on the lower-higher-modal truncation error of harmonic responses can be expressed as a sum of available modes and system matrices. A correction method, which onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…The finite element method (FEM) was used by Chen (2014) to analyze the impacts of the twist angle on inherent frequency, where the K-V damping effect was considered, whereas the explicit modal shapes and corresponding dynamic responses were not worked out. Liu et al. (2016) considered a nonclassically damped linear system with symmetric governing matrices, and because of the modal nonorthogonality, complex mode theory was introduced for equation decoupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finite element method (FEM) was used by Chen (2014) to analyze the impacts of the twist angle on inherent frequency, where the K-V damping effect was considered, whereas the explicit modal shapes and corresponding dynamic responses were not worked out. Liu et al. (2016) considered a nonclassically damped linear system with symmetric governing matrices, and because of the modal nonorthogonality, complex mode theory was introduced for equation decoupling.…”
Section: Introductionmentioning
confidence: 99%
“…(2003) also conducted an eigenvalue analysis of a nonproportional damped beam, and an expansion in state form was generated in conjunction with a transfer matrix technique. Such analyses were also performed in (Qu and Selvam, 2002; Li et al., 2016; Lzaro, 2016), wherein the governing matrices were uniformly symmetric, although the effects of nonproportional damping were included. Through this specific literature review, the following conclusions are drawn at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…Often, a lot of rolling machine parts such as blowers, engines and boosters may cause oscillatory excitation [1]. Therefore, harmonic response analysis is playing an increasingly important role in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect method to calculate the sensitivity of MAC values is based on the existing sensitivity method of mode shape. Several methods have been developed for the calculation of the sensitivity of mode shape, including the model method (Adhikari, 1999, 2002), the modified modal method (Wang, 1991; Li et al., 2014d; Zhang, 2014), Nelson’s method (Nelson, 1976; Friswell and Adhikari, 2000; Adhikari and Friswell, 2006; Li et al., 2012a, 2013a, 2013b; Weng et al., 2013), the algebraic method (Lee and Jung, 1997; Lee et al., 1999; Li et al., 2012b, 2014c), and the iterative method (Xie, 2012, 2013; Wu et al., 2015). Due to the fact that many design parameters are involved in practice and the diagonal elements of the MAC sensitivity matrix are usually considered, a direct method (Li et al., 2014a) was developed to efficiently and accurately calculate the sensitivity of MAC values.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of the damping influence in structural analysis is extremely important if a model is to be applied in predicting vibration levels, transmissibility, transient responses, and design problems dominated by energy dissipation. It was shown that complex modal analysis can be a good choice to accurately calculate the frequency response (Adhikari, 2013; Li et al., 2014b, 2014e) and can be used to transform any viscously damped system into independent second-order equations (Ma et al., 2010; Morzfeld et al., 2011; Kawano et al., 2013). The damped system produces a set of normal real mode shapes only when it satisfies the mathematical conditions (Caughey and O’Kelly, 1965).…”
Section: Introductionmentioning
confidence: 99%